Purification and characterization of Alanine dehydrogenase from Streptomyces anulatus for its application as a bioreceptor in biosensor. (May 2018) - Dave, Ushmaben Chandrakantbhai; Kadeppagari, Ravi-Kumar
Graphical abstract: Highlights: AlaDH of S. anulatus showed wide pH (5–11) and temperature (20–50 °C) working range. Enzyme retained over 95% of the activity at 4 °C on 120 th day in the presence of DTT. Ammonium biosensor was developed using AlaDH as a bioreceptor. Biosensor showed linear response for 0.1–300 mM NH4 + with 20 s response time. Abstract: Screening of different unexplored species of Streptomyces led to the identification of alanine dehydrogenase (AlaDH) from Streptomyces anulatus . This AlaDH was purified, characterized and was used as a bioreceptor for developing an ammonium biosensor that can detect ammonium ions in water samples. The AlaDH of S. anulatus was a dimer with each monomeric unit of Mol. Wt. 61 kDa. The optimum pH for AlaDH in oxidative deamination and reductive amination was 10 and 8.5 respectively with wide working pH range of 5–11. The optimum temperature was 40 °C in both the reactions with wide working temperature range of 20–50 °C. The enzyme retained more than 85% of its original activity after incubating at 60 °C for 30 min in the presence of DTT. Due to these properties of AlaDH, it was successfully used as a bioreceptor in the ammonium biosensor and the sensor showed linear response in the range of 0.1–300 mM NH4 + with the detection limit of 0.01 mM NH4 + and response time of 20 s. The sensor was showing good response at wide pH (5–11) and temperature range (20–50 °C) suggesting its usage at ambient and non-ambient conditions. The sensor was successfully validated with Nessler's reagent method by using real water samples.